2021
DOI: 10.1186/s13041-021-00875-7
|View full text |Cite
|
Sign up to set email alerts
|

VMAT2 availability in Parkinson’s disease with probable REM sleep behaviour disorder

Abstract: REM sleep behaviour disorder (RBD) can be an early non-motor symptom of Parkinson’s disease (PD) with pathology involving mainly the pontine nuclei. Beyond the brainstem, it is unclear if RBD patients comorbid with PD have more affected striatal dopamine denervation compared to PD patients unaffected by RBD (PD-RBD−). To elucidate this, we evaluated the availability of vesicular monoamine transporter 2 (VMAT2), an index of nigrostriatal dopamine innervation, in 15 PD patients with probable RBD (PD-RBD+), 15 PD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 52 publications
0
20
0
Order By: Relevance
“…Other studies examined general neuroimaging changes of the accumbens in PD during the course of disease such as reduction in VMAT2 density [ 257 ], lower gray matter volume [ 57 , 258 ] and a lower orientation dispersion of the amygdala accumbens pathway [ 62 ]. In an MRI-study, the volume of the ventral striatum was reduced in later-disease stages of PD as compared to earlier disease-stages.…”
Section: Regions Of the Limbic Systemmentioning
confidence: 99%
“…Other studies examined general neuroimaging changes of the accumbens in PD during the course of disease such as reduction in VMAT2 density [ 257 ], lower gray matter volume [ 57 , 258 ] and a lower orientation dispersion of the amygdala accumbens pathway [ 62 ]. In an MRI-study, the volume of the ventral striatum was reduced in later-disease stages of PD as compared to earlier disease-stages.…”
Section: Regions Of the Limbic Systemmentioning
confidence: 99%
“…Furthermore, the authors subsequently showed that de novo PD patients with RBD and patients with idiopathic RBD had significantly more symmetric nigrostriatal dopaminergic degeneration, possibly reflecting more symmetric α-synuclein spreading in the brainstem related to overlapping vagal innervation [ 79 ]. Interestingly, no difference in presynaptic VMAT2 and postsynaptic D2R dopaminergic function, using 11C-DTBZ and 11C-FLB-457, respectively, was found in PD patients with or without probable RBD, with the extrastriatal decline of 11C-FLB-457 binding in the temporal cortex, involving the uncus parahippocampus, superior, lateral, and inferior temporal cortex, although group size was limited [ 80 , 81 ].…”
Section: Neurotransmitter Imagingmentioning
confidence: 99%
“…There is a strong association between RBD and neurodegenerative disease, especially PD, in which the first manifestations of PD may be the RBD, necessitating careful follow-up of any patients presenting with RBD [41]. While routine neuroimaging, with magnetic resonance and computer tomography, is unlikely to contribute to the evaluation of RBD [41], more sophisticated evaluation, using [ 11 C]DTBZ PET imaging has shown that there is pathology, mainly involving the pontine nuclei [43] but it is unclear if those with RBD and PD have greater affected denervation of striatal dopamine when compared with PD patients who do not exhibit RBD [43]. Valli et al [43] examined availability of vesicular monoamine transporter 2 (VMAT2) which is an index of nigrostriatal dopamine innervation and reported that those with PD and RBD had lower availability of VMAT2, than did healthy controls, within the putamen, ventral striatum and globus pallidus but not within the substantia nigra or subthalamus.…”
Section: Rapid Eye Movement (Rem) Sleep Behaviour Disorder (Rbd)mentioning
confidence: 99%
“…While routine neuroimaging, with magnetic resonance and computer tomography, is unlikely to contribute to the evaluation of RBD [41], more sophisticated evaluation, using [ 11 C]DTBZ PET imaging has shown that there is pathology, mainly involving the pontine nuclei [43] but it is unclear if those with RBD and PD have greater affected denervation of striatal dopamine when compared with PD patients who do not exhibit RBD [43]. Valli et al [43] examined availability of vesicular monoamine transporter 2 (VMAT2) which is an index of nigrostriatal dopamine innervation and reported that those with PD and RBD had lower availability of VMAT2, than did healthy controls, within the putamen, ventral striatum and globus pallidus but not within the substantia nigra or subthalamus. When compared with those who had PD but not RBD, they concluded that VMAT2 and striatal dopamine denervation, in general, may not be a significant contributor to the pathophysiology of RBD in PD patients [43].…”
Section: Rapid Eye Movement (Rem) Sleep Behaviour Disorder (Rbd)mentioning
confidence: 99%
See 1 more Smart Citation